2023
DOI: 10.1097/gme.0000000000002211
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, tolerability, and endometrial safety of ospemifene compared with current therapies for the treatment of vulvovaginal atrophy: a systematic literature review and network meta-analysis

Abstract: Importance Ospemifene is a novel selective estrogen receptor modulator developed for the treatment of moderate to severe postmenopausal vulvovaginal atrophy (VVA). Objective The aim of the study is to perform a systematic literature review (SLR) and network meta-analysis (NMA) to assess the efficacy and safety of ospemifene compared with other therapies used in the treatment of VVA in North America and Europe. Evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Endometrial thickness ranged between 2.1 and 2.3 mm at baseline and 2.5 and 3.2 mm after treatment. 18 Placebo-controlled trials as well as real-life use of ospemifene have not shown an increase in venous thromboembolism among ospemifene using women when compared to non-ospemifene using women. 16,19…”
Section: Safety Profilementioning
confidence: 96%
See 2 more Smart Citations
“…Endometrial thickness ranged between 2.1 and 2.3 mm at baseline and 2.5 and 3.2 mm after treatment. 18 Placebo-controlled trials as well as real-life use of ospemifene have not shown an increase in venous thromboembolism among ospemifene using women when compared to non-ospemifene using women. 16,19…”
Section: Safety Profilementioning
confidence: 96%
“…Preclinical data, clinical data and systematic review have demonstrated ospemifene's antiestrogenic effect and its safety profile with regard to breast tissue, inhibiting tumor growth and possible chemoprotective effect. [17][18][19] Ospemifene is the only therapeutic option approved for use in women with VVA and a history of breast cancer. 26…”
Section: Specific Patient Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ospemifene is a selective estrogen receptor modulator that is FDA approved for vaginal atrophy [ 87 , 89 ]. Data in the general population are promising [ 93 , 94 ], along with data that do not demonstrate increased recurrence rates in breast cancer survivors (although not FDA recommended in breast cancer survivors due to lack of data) [ 95 ]. Careful consideration must be given due to ospemifene’s agonist effects on endometrial tissue and increased risk of VTE [ 96 ].…”
Section: Treatment Of Menopausal Symptomsmentioning
confidence: 99%
“…Steven R. Goldstein, MD, CCD, NCMP, FACOG, FRCOG(H) I n this month's journal, the article by Simon et al 1 deals with a systematic review of the efficacy and safety of ospemifene compared with current therapies for the treatment of vulvovaginal atrophy. They included 44 controlled trials involving 12,637 participants.…”
Section: Endometrial Safety and Efficacy Of Ospemifenementioning
confidence: 99%